Front Cover: Iron–PNP‐Pincer‐Catalyzed Transfer Dehydrogenation of Secondary Alcohols (ChemSusChem 13/2019). Issue 13 (4th July 2019) - Budweg, Svenja; Wei, Zhihong; Jiao, Haijun; Junge, Kathrin; Beller, Matthias
Abstract : The Front Cover shows the transfer dehydrogenation of secondary alcohols with a well‐defined iron–PNP‐pincer complex. In this study, acetone is used as inexpensive hydrogen acceptor. This enables the oxidation under mild conditions with good‐to‐excellent yields of the corresponding ketones. More information can be found in the Communication by Budweg et al on page 2988 in Issue 13, 2019 (DOI: 10.1002/cssc.201900308 ).